Acción del Cloramfenicol sobre el embrión de pollo - Pacheco de Arauz, Gloria (1976)
The most important effects of Chloramphenicol in several groups of 72- and 96-hour-old chick embryos are: (a) inhibition of growth expressed by termination of stages of reached development and the compared mortality between the different groups; (b) appearance of macro- and microscopic hemorrhages of the parenchyma of organs and connective tissues; and, (c) absence of vascular continuity and the presence of immature red cells in the tissues. While these anomalies may not be caused by the drug, since they occur in the same percentages between the groups treated with chloramphenicol and those with distilled water, their severity could be attibuted to the various concentrations of the drug.